Interventional Affecting Hemostasis Time after Arteriovenous Fistula Needle Removal in Hemodialysis Patients: A Meta-Analysis - Yunia Tri Prasetyani; Arif Setyo Upoyo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hemostasis following arteriovenous fistula (AVF) needle removal is a key determinant of vascular access outcomes in hemodialysis patients. This meta-analysis aimed to evaluate the effect of hemostatic dressings and needle bevel position on hemostasis time following arteriovenous fistula (AVF) needle removal in hemodialysis patients. This meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of eight electronic databases identified randomized controlled trials and quasi-experimental studies published between January 2016 and June 2025. Eligible studies evaluated the effects of hemostatic dressings and needle bevel position on hemostasis time following AVF needle removal in adult hemodialysis patients. Study quality was assessed using the Joanna Briggs Institute critical appraisal tools. Due to substantial heterogeneity, random-effects meta-analyses were performed, and standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated. Seven studies met the inclusion criteria. Three studies evaluating hemostatic dressings demonstrated a significant reduction in hemostasis time at arterial sites (SMD = −1.23, 95% CI −2.36 to −0.11; p=0.032) and venous sites (SMD = −1.35, 95% CI −2.16 to −0.54; p=0.001). Four studies assessing needle bevel position showed that the bevel-down position significantly reduced hemostasis time compared with the bevel-up position (SMD = −1.30, 95% CI −2.45 to −0.14; p=0.028). All pooled analyses exhibited high heterogeneity.